Alteration zonation in the Loma Blanca kaolin deposit, Los Menucos, Province of Rio Negro, Argentina - Marfil, Silvina Andrea (2010)
The Loma Blanca mine is in one of the northwest kaolinized zones of the Los Menucos area (Patagonia, Argentina). The parent rocks are andesites and andesitic tuffs from the Vera Formation, Los Menucos Group (Lower Triassic). Hayase & Maiza (1974) proposed a concentric zonation model. From the parent rock outward, four different alteration patterns were recognized: Zone 1, with sericite, chlorite and montmorillonite; Zone 2, with kaolinite and dickite; Zone 3, with dickite, pyrophyllite and alunite; and Zone 4, with quartz, disseminated sulphides and diaspore. The relationship between the chemical composition of major, minor and trace elements and the mineralogical alteration zonation was evaluated to confirm the genesis of the deposit. Fe2O3, CaO, Na2O and K2O contents decrease from Zone 1 to Zone 3, whereas Al2O3 and LOI increase in the kaolinite-alunite zone. In the chemical composition of alunite, Na > K. Large Ba, Sr, V and Zr contents were observed mainly in Zones 2 and 3. Co, Ni, Cu, Zn and Rb are more common in Zone 1. LREE are more abundant than HREE in Zones 2 and 3. In kaolinites d18O values range from 10.8% to 13.2%, and dD from 83% to 85%. The mineral assemblage (dickite-alunite-pyrophyllite-diaspore), the alteration zonation pattern (laterally concentric), the geochemistry of trace elements, the relation between LREE and HREE and the small d18O values suggest that the Loma Blanca deposit was formed by hydrothermal processes.